PROSPECTIVE TEACHERS’ STUDENTS' PERSPECTIVE REGARDING THE USE OF WEB-BASED GAMIFICATION AS LEARNING MEDIA - Asriati, Asriati; Asriadi, Muhammad (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2023)
This study investigates prospective teachers’ perspectives of web-based gamification applications used as classroom learning media. This study used a mixed method. 65 students participated as questionnaire respondents, and among the respondents, 3 students who got more than a 3.85 GPA from the third-year students were purposively chosen to be the participants. They willingly participated as participants in this study. A questionnaire and an in-depth interview are the techniques to gather the data. The results reveal that the participants in this study thought that using web-based gamification applications as learning media was beneficial and influential for them. As learning media, they use web-based gamification applications such as Quizziz, Kahoot, Wordwall, and others in their teaching. Their students find the game attractive and enchanting. Although they are useful media to attract and motivate students in the teaching and learning process, the participants also mark that free access to the game might have a negative impact on both teachers and students. From their perspectives as high achievers’ students, web-based gamification also has a certain role in improving their understanding and maintaining their focus during the teaching and learning process.